Normative values of handgrip strength in adolescents according to chronological age and sexual maturation - Mateus Augusto Bim; André de Araújo Pinto; Diego Augusto Santos Silva; Anna Mestriner Rodrigues; Andreia Pelegrini (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: Handgrip strength is considered an important health indicator. It is extremely important to establish normative values so that the handgrip strength is correctly interpreted in adolescents. The present study aims to establish normative values of handgrip strength (HGS) for adolescents, according to chronological age and sexual maturation. Methods: Data from three large projects carried out in Florianopolis and São José, Santa Catarina were used, corresponding to a sample of 2,637 adolescents aged 14 to 19 years old of both sexes (1,428 girls). The HGS of the right and left hands was measured by a manual dynamometer, and total HGS being defined by the sum of the left hand and the right-hand strength. Sexual maturation was determined by the development of pubic hair. The percentiles 3, 10, 15, 25, 50, 75, 85, 90, and 97 were calculated for the right, left, and total HGS. The percentile ranges < p15 (low), p15-p85 (normal) and > p85 (high) were used. ANOVA and Kruskal-Wallis tests were applied. Results: In boys, the mean total HGS ranged from 67.5 ± 16.5 to 86.9 ± 21.8 (p < 0.001) and 74.3 ± 17.5 to 82.2 ± 17.8 (p < 0.001) for age and sexual maturation, respectively, while in girls the mean HGS total ranged from 48.8 ± 11.3 to 56.4 ± 16.0 (p = 0.127) and 47.8 ± 10.6 to 54.3 ± 12.3 (p < 0.001). Conclusion: Reference values established by the percentile score, can be used to identify adolescents with better athletic condition and can be useful for prescribing exercises.